2012 19th IEEE International Symposium on the Physical and Failure Analysis of Integrated Circuits 2012
DOI: 10.1109/ipfa.2012.6306298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and TCAD simulation of 90 nm technology transistors under continous photoelectric laser stimulation for failure analysis improvement

Abstract: This study is driven by the need analysis methodologies based on laser/silicon the functional response of an integrated cir stimulation. It is therefore mandatory to under of elementary devices to laser illumination, in predict the behavior of more complex cir characterizes and analyses photoelectric effect 1064 nm wavelength laser on a 90 nm transistor. Comparisons between photocurren channel transistor, or in function of its sta presented. Experimental measurements are c Elements Modeling Technology Computer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
2
7
0
Order By: Relevance
“…Their shapes exhibit a Gaussianlike behavior. It makes it possible to extract a mathematical model based on the sum of two Gaussian functions (4), where d is the distance between the spot and the closest edge of the junction expressed in micrometer: (4) For each lens, the coefficients β, γ, c 1 and c 2 were found different (see Table II).…”
Section: ) Study Of the Spatial Dependence A) Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Their shapes exhibit a Gaussianlike behavior. It makes it possible to extract a mathematical model based on the sum of two Gaussian functions (4), where d is the distance between the spot and the closest edge of the junction expressed in micrometer: (4) For each lens, the coefficients β, γ, c 1 and c 2 were found different (see Table II).…”
Section: ) Study Of the Spatial Dependence A) Measurementmentioning
confidence: 99%
“…Former electrical models of NMOS transistors u n d e r pulsed-laser stimulation were generally m a d e o f a simple current source which represents the photocurrent induce by the laser [3]. We have already introduced electrical models for continuous illumination at small laser power (below ~100mW), which only consider photoelectrical effects [4], [5], [6], [7]. The novelty of the model presented in this paper is that it takes into accounts the laser's parameters (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These models were built and validated from actual measurements on transistors. This research work is reported in [5,6]. The current amplitude of the current source of each PN junction is defined thanks to equations presented on Table I.…”
Section: B Electrical Modelingmentioning
confidence: 99%
“…Electrical models of PN junctions under pulsed laser stimulation (N+ on Psubstrate, P+ on Nwell and Nwell on Psubstrate) were previously introduced [4,5]. We have also already introduced electrical models, based on preliminary studies made from measurements and TCAD simulations [6,7] for continuous PLS at low laser power (under ~100 mW), which create only photoelectrical effects [8,9]. This model consists in a simple current source controlled by voltage to model the laser induced photocurrent.…”
Section: Introductionmentioning
confidence: 99%
“…Electrical models of PN junctions under pulsed PLS (N+ on Psubstrat and P+ on Nwell) were previously introduced [2]. We have also already introduced electrical models, based on preliminary studies made from measurements and TCAD simulations [3,4] for continuous PLS at laser power under ~100mW, which create only photoelectrical effects [5,6]. This model consists in a simple current source controlled by voltage to model the laserinduced photocurrent.…”
Section: Introductionmentioning
confidence: 99%